Strategi Komunikasi Pemasaran Produk Kerajinan Anyaman Umkm Rumah Anyam Krisajo Di Desa Sambirejo Kecamatan Jiwan Kabupaten Madiun - Mohamad Afwan Ghoffar; Tanti Hermawati (Jurnal Komunikasi Massa, 2024)
UMKM Rumah Anyam Krisajo, located in Desa Sambirejo, Kecamatan Jiwan, Kabupaten Madiun, not only plays a role as a driver of the local economy by creating job opportunities and business prospects but also serves as a guardian of cultural heritage by introducing traditional weaving arts to a broader market. This study aims to analyze the marketing communication strategies employed by Umkm Rumah Anyam Krisajo in promoting their weaving products in Desa Sambirejo, Kecamatan Jiwan, Kabupaten Madiun. The research uses a qualitative method with a marketing communications mix theory approach. The study involves five key informants, including the manager of Rumah Anyam Krisajo, consumers, and partners involved in product marketing. Purposive sampling was used to select the informants. The findings reveal that in executing its marketing communication process, Rumah Anyam Krisajo undertakes several planning stages, including identifying communicators, analyzing audience needs, crafting messages, selecting media and communication channels, and evaluating communication effects. The implementation of marketing communication strategies encompasses six main aspects: sales promotion, events and experiences, public relations and publicity, interactive marketing, word-of-mouth marketing, and personal selling. This study is expected to provide deeper insights into the effectiveness of marketing communication strategies used by SMEs in reaching their market and promoting their products more broadly and efficiently.